Implementing Resource, Description, and Access in a time of change in the small academic library. Issue 4 (1st October 2016) - Perez-Lizano, Elena
Abstract : The new cataloging standard, Resource, Description, and Access, has forced many libraries to rethink how metadata is displayed and accessed. Although Resource, Description, and Access implementation may seem daunting at first, especially for small libraries with shrinking staff and budgets, implementation provides an excellent opportunity to re-evaluate legacy workflows and work collaboratively as a group to develop policies and procedures that will ultimately help the library become more responsive to change. In this article the author examines these challenges in a small academic library and how to overcome them with training, practice, and time. Both general and specific guidelines are discussed for Resource, Description, and Access implementation in the small academic library.